Factors affecting students' speaking skills acquisition among Malaysian undergraduates French foreign language learners - Berbiche Mariama (2020)
The present study is intended to investigate the problems encountered by Malaysian learners undertaking French as a foreign language in higher education institution in Malaysia. This study is to identify the factors that affect the development of learners’ speaking ability and find how these factors have contributed to the hindrance of learners’ speaking. The study also aims to suggest some solutions and strategies that can help Malaysian French foreign language learners to overcome these problems. To gain an in-depth understanding on the problem the researcher carried out this study using Multi-Methods design whereby the participants were investigated twice to examine and analyze the research problem from different angle employing questionnaire and semi-structured interviews. The researcher used probability sampling to collect the quantitative data from (115) participants and used the purposive sampling to collect the qualitative data which consist of ten participants. From the quantitative findings, only motivation was found as a factor that prevents Malaysian French foreign language learners from speaking in French language contrarily to the qualitative findings it was revealed that motivation, anxiety, and teacher’s role are affecting Malaysian French foreign language learners speaking skill acquisition. Accordingly, these three factors are a real issue as they hinder Malaysian French foreign language learners to achieve their goal of learning French after completing their French course.